HUBUNGAN AKTIVITAS FISIK DENGAN KUALITAS TIDUR PADA PASIEN DIABETES MELITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS II DENPASAR BARAT - Komang Hadpani; Desak Made Widyanthari; Made Oka Ari Kamayani (Coping: Community of Publishing in Nursing, 2020)
Diabetes Mellitus (DM) is a metabolic disorder because the pancreas does not produce enough insulin or body does not capable to use insulin effectively. Poor sleep quality is often happens in patient with type 2 DM because of the sleep disorder. One of the effort to increasing sleep quality are by doing physical activities. This studi aimed to determine the correlation between physical activities and sleep quality among patients with Type 2 Diabetes Mellitus at wilayah kerja Puskesmas II Denpasar Barat. This study was a descriptive correctional and cross sectional study model approach. The samples in this study are 30 respondents obtained with purposive sampling methods. Physical activities and sleep quality data are used the International Physical Activity Questionnare and Pittsburgh Sleep Quality Index Questionnare. The result of the Spearman Rank correlation test showed that are positif relation between physical activities and sleep quality of patient with Type 2 DM at wilayah kerja Puskesmas II Denpasar Barat (r = 0.817; p=0.01), which means that lower physical activity, the worse the sleep quality of patients with type 2 DM. The result of this research is expected to be used as a guide in observing daily physical activities for increasing sleep quality.